A review of the Department of Health and Social Care's Funding Reform Model - Rowena Crawford; Polly Simpson (Institute for Fiscal Studies (IFS), 2018)
The Department of Health and Social Care (DHSC) is responsible for setting the overall direction for social care policy and funding in England. Recently DHSC has developed in-house modelling capacity to examine likely implications of possible reforms to the system for funding social care. This departs from the process used by the Dilnot Commission on the Funding of Care and Support, where modelling of the implications of the proposed reforms was commissioned from the Public Social Services Research Unit (PSSRU) at the University of Kent and the London School of Economics. Given the complexity of the models involved, the many uncertainties and data constraints, and the high level use of the outputs produced, good quality assurance is vital. The DHSC does much internal quality assurance, but understandably (and commendably) decided to commission an independent external review of the department's modelling approach. This paper writes up our main findings from that review. This review has focused on the DHSC's Adult Social Care "Funding Reform Model" (referred to throughout as the "FRM"). This model is used to examine state funding for social care under proposed funding systems as compared with the current system, and conduct distributional analysis of proposed reforms. The FRM interacts closely with the PSSRU's Aggregate Demand Model, and the outputs of the FRM are combined with DHSC's "Long Term Demand" (LTD) model to produce projections for the future level of state spending on social care under different funding systems. We have not reviewed these models in detail, but have considered the implications of the way they interact with the FRM.
Keywords: 330